An assessment of knowledge and awareness on hepatitis B and hepatitis C viruses among police trainees attending police training college, Ongole, Prakasam District, Andhra Pradesh, India - Venkateswarlu, Devarakonda; Rao, Burri T.; Manasa, Devarakonda; Chowdhary, Ravi Y. (International Journal Of Community Medicine And Public Health, 2021)
Background: HBV and HCV are blood borne viral diseases, and knowledge about modes of transmission and preventive aspects can help in reduce the risk of getting liver diseases and mainly transmitted through transfusion of contaminated blood and blood products. The knowledge regarding HBV and HCV infection studied in many professional groups, but few surveys are available among the police professionals. The study was conducted to assess the knowledge and awareness regarding Hepatitis B and C viruses’ transmission among these police trainees, and to find out the awareness regarding symptoms, signs, complications and importance of Hepatitis B vaccine. Methods: A cross sectional observationalstudywasconductedamongthepolicetraineesattendingdistrictpolicetraining college, Ongole, Prakasam district, Andhra Pradesh. Information about socio demographic characteristics, basic knowledge about hepatitis B and C viruses, its modes of transmission, prevention, symptoms and signs and also complications, Hepatitis B vaccination were also assessed from all these police trainees. The data were collected, tabulated, and statistically analyzed. Results: Among total police trainees 61.8% belong to upper middle class, 62.4% were degree holders and most of them belonging to Krishna (32.2%) district. About 59% of police trainees aware about hepatitis B virus infection and 67% know about hepatitis C virus infection. 67.2% were listen about availability of hepatitis B vaccination, none of the participants were aware about hepatitis B vaccine zero dose schedule. Conclusions: Efficient health programme managing departments must take the responsibility for HBV education, transmission, testing, vaccination accessibility and availability.